The Commodity Form of Safety Information - Rodrigo Finkelstein (tripleC: Communication, Capitalism & Critique)
The production of safety information is deemed a vital resource to protect human lives at the work site. The injury rate, lost days, incapacity rate, and fatality rate, are key indicators to prop up labour risk awareness and identify job hazards. However, safety information gets highly distorted because it does not only measure risk but serves as a means of exchange. It determines the amount of money to be swapped between Workers’ Compensation Boards and their client corporations. Moreover, as a depository of exchange value, safety information tends to exert pressure over social reality rather than just being a passive reflection of it. This paper discloses the commodity form of safety information. Based on a political economy of information framework, it identifies, describes, and analyses the safety information commodity in its active role of organizing safety and labour health.